IMPLEMENTATION OF FAMILY PLANNING PROGRAM THROUGH MALE PARTICIPATION IN THE USE OF CONTRACEPTIVE METHODS IN MEDAN KOTA SUB-DISTRICT MEDAN CITY - Harahap, Iskandar Muda Agung; Ginting, Simson (DIA: Jurnal Administrasi Publik, 2025)
Despite the availability of various contraceptive methods, men’s participation in the family planning programme is still limited, mainly due to cultural and religious considerations towards the vasectomy method. In addition, family planning services for men are still dominated by women as Family Planning Field Instructors (PLKB). This has resulted in men being reluctant to consult in its implementation. This raises a question mark as to why the Family Planning Programme is not so visible among the community? The purpose of this research is to find out how the implementation of family planning programme through men’s participation in the use of contraceptive methods in Medan City Sub-district, Medan City. The method used is descriptive research method with qualitative approach. The data were analysed qualitatively using the Merilee S. Grindle Model with two main variables, namely policy content and policy environment. The results concluded from the policy content indicator showed that Medan Kota Sub-district really needed a family planning programme because the number of poor people in Medan Kota Sub-district was still a concern, and from the policy environment indicator showed that there was full support from the government regarding long-term family planning methods.